Polymer composition for use in camera module
Patent Information
- Application Number
- JP2024202942
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-02-20
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-11
Smart Images

Figure 2025032139000001_ABST
Abstract
Description
[Technical field]
[0001]
[0001] This application claims the benefit of U.S. Provisional Patent Application No. 62 / 821,086, having a filing date of March 20, 2019; U.S. Provisional Patent Application No. 62 / 885,338, having a filing date of August 12, 2019; and U.S. Provisional Patent Application No. 62 / 978,849, having a filing date of February 20, 2020, all of which are incorporated by reference in their entireties. [Background technology]
[0002]
[0002] Camera modules (or components) are often used in mobile phones, laptop computers, digital cameras, digital video cameras, and the like. Generally, a camera module includes a lens module and an image sensor for converting an image of an object into an electrical signal. The lens module may be disposed in a housing and may include a lens barrel with one or more lenses disposed therein. Additionally, the camera module may include an actuator assembly for optical image stabilization (OIS) that reduces loss of resolution or blur caused by camera shake. The actuator assembly functions by moving the lens module to a target position after receiving a specific signal. To help ensure proper alignment of the lens module during movement, many actuator assemblies also include ball bearings that help guide the lens module in a desired direction. Traditionally, these ball bearings are made of a ceramic material that is tough enough to withstand the forces applied during use. However, while the ball bearings are tough, they can also form "dimples" on the surface of the camera module, which can create noise and affect performance. Summary of the Invention [Problem to be solved by the invention]
[0003]
[0003] Therefore, there is a need for materials that can exhibit better performance when used in camera modules. [Means for solving the problem]
[0004] According to one embodiment of the present invention, a camera module is disclosed that includes a polymer composition that includes a polymer matrix that includes a liquid crystal polymer and an inorganic filler. The liquid crystal polymer includes repeat units derived from naphthenic hydroxy carboxylic acids and / or dicarboxylic acids in an amount of about 10 mole % or more of the polymer. Further, the polymer composition has a 400 s .sup.2 melting point of 100 s according to ISO test number 11443:2005. -1 The composition has a melt viscosity of about 30 to about 400 Pa·s when measured at a shear rate of about 100° C. and a temperature 15° C. higher than the melting point of the composition.
[0005]
[0005] In accordance with another embodiment of the present invention, a polymer composition for use in a camera module is disclosed. The composition includes a liquid crystal polymer, the liquid crystal polymer including about 20% to about 70% by weight of a polymer matrix including repeat units derived from naphthenic hydroxy carboxylic acid and / or dicarboxylic acid in an amount of about 10 mole % or more of the polymer; about 1% to about 40% by weight of inorganic fibers; and about 2% to about 50% by weight of inorganic particles. The polymer composition also has a 400 second melting point according to ISO test number 11443:2005. -1 and a temperature 15° C. higher than the melting point of the composition, the composition has a melt viscosity of about 30 to about 400 Pa·s.
[0006]
[0006] Other features and aspects of the present invention are set forth in more detail below.
[0007] The appended claims are intended to provide a complete and enabling disclosure of this invention, including the best mode thereof, to one of ordinary skill in the art. This is shown in more detail in the remainder of the specification, including reference to the accompanying drawings. [Brief description of the drawings]
[0007] [Figure 1]
[0008] FIG. 1 is a perspective view of a camera module that can be formed in accordance with one embodiment of the present invention. [Diagram 2]
[0009] FIG. 2 is a top perspective view of an embodiment of an electronic device including a camera module of the present invention. [Diagram 3]
[0010] FIG. 3 is a bottom perspective view of the electronic device shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008]
[0011] It will be understood by those skilled in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the invention.
[0012] Generally speaking, the present invention relates to a polymer composition for use in a camera module. The polymer composition comprises inorganic fibers dispersed within a polymer matrix comprising a liquid crystal polymer. The inventors have found that by selectively controlling the specific properties of the inorganic fibers and the liquid crystal polymer, the resulting composition can exhibit a unique combination of flexural strength and hardness that allows it to be more easily used in a camera module. For example, the melt viscosity of the polymer composition can be sufficiently low so that the polymer composition can easily flow into a mold cavity having small dimensions. In one particular embodiment, the polymer composition is melted at 400 s. -1 The composition may have a melt viscosity of about 30 to about 400 Pa·s, in some embodiments about 40 to about 250 Pa·s, in some embodiments about 50 to about 220 Pa·s, and in some embodiments about 60 to about 200 Pa·s, measured at a shear rate of about 100° C. to about 300° C. Melt viscosity may be measured at a temperature 15° C. above the melting point of the composition (e.g., 305° C.) according to ISO Test No. 11443:2005.
[0009]
[0013] It was previously believed that compositions with such low melt viscosities also did not have sufficiently good mechanical properties to enable their use in camera modules. However, the present inventors have found that, contrary to conventional belief, the polymer compositions of the present invention can still achieve excellent mechanical properties. For example, the polymer compositions may exhibit a flexural modulus of about 7,000 MPa or more, in some embodiments about 9,000 MPa or more, in some embodiments about 10,000 MPa to about 30,000 MPa, and in some embodiments about 12,000 MPa to about 25,000 MPa, as determined at 23° C. according to ISO test number 178:2010 (technically equivalent to ASTM-D790-10). The polymer compositions may also exhibit a Rockwell surface hardness of about 25 or more, in some embodiments about 35 or more, in some embodiments about 45 or more, and in some embodiments about 55 to about 100, as determined according to ASTM-D785-08 (scale M). Further, when subjected to the "ball indentation" test described herein, the polymeric compositions may exhibit indentations of only about 50 micrometers or less, in some embodiments, about 45 micrometers or less, in some embodiments, about 1 to about 40 micrometers, in some embodiments, about 1 to about 20 micrometers, in some embodiments, about 1 to about 10 micrometers, and in some embodiments, about 1 to about 5 micrometers, as determined using a metal ball having a diameter of 1.5 mm and a weight of 75 grams. Of course, when tested using a ball of smaller weight (e.g., 35 or 50 grams), the polymeric compositions may also exhibit indentations within the above ranges. Further, when subjected to the "mini drop" test described herein, the polymeric compositions may exhibit indentations of only about 50 micrometers or less, in some embodiments, about 45 micrometers or less, in some embodiments, about 1 to about 40 micrometers, in some embodiments, about 1 to about 20 micrometers, and in some embodiments, about 1 to about 50 micrometers, as determined using a metal ball having a diameter of 1.5 mm and a weight of 5 grams, for 20,000 drops from a height of 150 millimeters. In some embodiments, the polymer composition may exhibit a depression of from about 1 to about 10 micrometers, and in some embodiments, from about 1 to about 5 micrometers. Of course, when tested using a smaller number of drops (e.g., 10,000 drops), the polymer composition may also exhibit a depression within the above ranges.
[0010]
[0014] The composition also has a thermal conductivity of about 2 kJ / m2 as determined at 23° C. according to ISO Test No. 179-1:2010 (technically equivalent to ASTM-D256-10e1). 2 In some embodiments, from about 4 to about 40 kJ / m 2 In some embodiments, from about 8 to about 30 kJ / m 2 The compositions may also exhibit a Charpy unnotched and / or notched impact strength of from about 20 to about 500 MPa, in some embodiments from about 50 to about 400 MPa, and in some embodiments, from about 60 to about 350 MPa; a tensile break strain of at least about 0.5%, in some embodiments, from about 0.8 to about 15%, and in some embodiments, from about 1 to about 10%; and / or a tensile modulus of from about 5,000 MPa to about 30,000 MPa, in some embodiments, from about 7,000 MPa to about 25,000 MPa, and in some embodiments, from about 10,000 MPa to about 20,000 MPa. Tensile properties may be determined at 23° C. according to ISO Test No. 527-1:2012 (technically equivalent to ASTM-D638-14). The compositions may also exhibit a flexural strength of about 40 to about 500 MPa, in some embodiments about 50 to about 400 MPa, in some embodiments about 100 to about 350 MPa, and / or a flexural break strain of about 0.5% or more, in some embodiments about 0.8% to about 15%, in some embodiments about 1% to about 10%. The flexural properties may be determined at 23° C. according to ISO Test No. 178:2010 (technically equivalent to ASTM-D790-15e2). The compositions may also exhibit a deflection temperature under load (DTUL) of about 180° C. or more, in some embodiments about 190° C. to about 280° C., measured at a specified load of 1.8 MPa according to ASTM-D648-07 (technically equivalent to ISO Test No. 75-2:2013).
[0011]
[0015] In addition to having good mechanical properties and low melt viscosity, the composition of the present invention has been found to have other properties that allow it to be more easily used in camera modules. For example, the polymer composition can exhibit a low degree of surface friction, which can minimize the degree to which the skin layer delaminates during use of the guide unit. For example, the polymer composition can exhibit a dynamic coefficient of friction of about 1.0 or less, in some embodiments about 0.4 or less, in some embodiments about 0.35 or less, and in some embodiments about 0.1 to about 0.3, as determined according to VDA-230-206:2007. Also, the wear depth can be about 500 micrometers or less, in some embodiments about 200 micrometers or less, in some embodiments about 100 micrometers or less, and in some embodiments about 10 to about 70 micrometers, as determined according to VDA-230-206:2007. Furthermore, the composition can also exhibit excellent antistatic behavior, especially when antistatic fillers are included in the polymer composition discussed above. Such antistatic behavior can be characterized by a relatively low surface and / or volume resistivity as determined according to IEC-60093. For example, the present compositions have a surface and / or volume resistivity of about 1×10 15 ohms or less, in some embodiments about 1×10 14 ohms or less, in some embodiments about 1×10 10 ohms ~ approx. 9 x 10 13 ohms, in some embodiments, about 1×10 11 ~Approx. 1×10 13 The composition may exhibit a surface resistivity of about 1×10 15 ohm·m or less, in some embodiments about 1×10 9 ohm·m~approx. 9×10 14 Ohm m, in some embodiments, approximately 1×10 10 ~Approx. 5×10 14 The composition may also exhibit a volume resistivity of about 1×10 ohms·m. Of course, such antistatic behavior is by no means required. For example, in some embodiments, the composition may exhibit a volume resistivity of about 1×1015 ohms or more, in some embodiments about 1×10 16 ohms or more, in some embodiments about 1×10 17 ohms ~ approx. 9 x 10 30 ohms, in some embodiments, about 1×10 18 ~ Approximately 1×10 26 It may exhibit a relatively large surface resistivity, such as an ohm.
[0012]
[0016] Various embodiments of the invention will now be described in more detail. I. Polymer Composition A. Polymer Matrix
[0017] The polymer matrix typically comprises one or more liquid crystal polymers, generally in an amount of about 15% to about 85% by weight, in some embodiments about 20% to about 75% by weight, and in some embodiments about 30% to about 50% by weight of the total polymer composition. Liquid crystal polymers having a high degree of crystallinity that allows them to effectively fill the small spaces in the mold are particularly suitable. Liquid crystal polymers are generally classified as "thermotropic" insofar as they have a rod-like structure and can exhibit crystalline behavior in their molten state (e.g., a thermotropic nematic state). The liquid crystal polymers used in the present polymer composition typically have a melting point of about 200°C or higher, in some embodiments about 220°C to about 350°C, and in some embodiments about 240°C to about 300°C. The melting point can be determined using differential scanning calorimetry (DSC), for example, by ISO test number 11357-3:2011 (melting point), as is well known in the art. Such polymers can be formed from one or more types of repeating units, as is well known in the art. Liquid crystal polymers generally have the following formula (I):
[0013] [ka]
[0014] (In the formula, Ring B is a substituted or unsubstituted 6-membered aryl group (e.g., 1,4-phenylene or 1,3-phenylene), a substituted or unsubstituted 6-membered aryl group fused to a substituted or unsubstituted 5- or 6-membered aryl group (e.g., 2,6-naphthalene), or a substituted or unsubstituted 6-membered aryl group bonded to a substituted or unsubstituted 5- or 6-membered aryl group (e.g., 4,4-biphenylene); Y1 and Y2 are independently O, C(O), NH, C(O)HN, or NHC(O). The aromatic ester may include one or more aromatic ester repeat units represented by:
[0015]
[0018] Typically, at least one of Y1 and Y2 is C(O). Examples of such aromatic ester repeat units include, for example, aromatic dicarboxylic acid repeat units (in formula I, Y1 and Y2 are C(O)), aromatic hydroxycarboxylic acid repeat units (in formula I, Y1 is O and Y2 is C(O)), and various combinations thereof.
[0016]
[0019] For example, 4-hydroxybenzoic acid; 4-hydroxy-4'-biphenylcarb 2-Hydroxy-6-naphthoic acid; 2-Hydroxy-5-naphthoic acid; 3-Hydroxy 2-Hydroxy-2-naphthoic acid; 2-Hydroxy-3-naphthoic acid; 4'-Hydroxyphenyl Aromatic hydroxycarboxylic acid repeat units derived from aromatic hydroxycarboxylic acids such as 3'-hydroxyphenyl-4-benzoic acid; 3'-hydroxyphenyl-4-benzoic acid; 4'-hydroxyphenyl-3-benzoic acid, and the like, as well as alkyl, alkoxy, aryl and halogen substituents thereof, and combinations thereof, can be used. Particularly preferred aromatic hydroxycarboxylic acid repeat units are Hydroxycarboxylic acids are 4-hydroxybenzoic acid ("HBA") and 6-hydroxy-2-naphthoic acid ("HNA"). When used, repeat units derived from hydroxycarboxylic acids (e.g., HBA and / or HNA) typically comprise at least about 50 mol %, in some embodiments at least about 60 mol %, and in some embodiments, from about 80 mol % to 100 mol % of the polymer.
[0017]
[0020] Aromatic dicarboxylic acid repeating units derived from aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, diphenyl ether-4,4'-dicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 4,4'-dicarboxybiphenyl, bis(4-carboxyphenyl)ether, bis(4-carboxyphenyl)butane, bis(4-carboxyphenyl)ethane, bis(3-carboxyphenyl)ether, bis(3-carboxyphenyl)ethane, etc., and alkyl, alkoxy, aryl, and halogen-substituted versions thereof, and combinations thereof, can also be used. Particularly suitable aromatic dicarboxylic acids include, for example, terephthalic acid (TA), isophthalic acid (IA), and 2,6-naphthalenedicarboxylic acid (NDA). If used, repeat units derived from aromatic dicarboxylic acids (e.g., IA, TA, and / or NDA) typically comprise from about 1 mol % to about 50 mol %, in some embodiments from about 2 mol % to about 40 mol %, and in some embodiments, from about 5 mol % to about 30 mol % of the polymer.
[0018]
[0021] Other repeat units can also be used in the polymer. For example, in some embodiments, repeat units derived from aromatic diols such as hydroquinone, resorcinol, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 4,4'-dihydroxybiphenyl (or 4,4'-biphenol), 3,3'-dihydroxybiphenyl, 3,4'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl ether, bis(4-hydroxyphenyl)ethane, and the like, as well as alkyl, alkoxy, aryl, and halogen-substituted versions thereof, and combinations thereof can be used. Particularly suitable aromatic diols include, for example, hydroquinone (HQ) and 4,4'-biphenol (BP). When used, repeat units derived from aromatic diols (e.g., HQ and / or BP) typically constitute about 1 mol % to about 30 mol %, in some embodiments, about 2 mol % to about 25 mol %, and in some embodiments, about 5 mol % to about 20 mol % of the polymer. Repeat units such as those derived from aromatic amides (e.g., acetaminophen (APAP)) and / or aromatic amines (e.g., 4-aminophenol (AP), 3-aminophenol, 1,4-phenylenediamine, 1,3-phenylenediamine, etc.) can also be used. When used, repeat units derived from aromatic amides (e.g., APAP) and / or aromatic amines (e.g., AP) typically comprise from about 0.1 mol % to about 20 mol %, in some embodiments from about 0.5 mol % to about 15 mol %, and in some embodiments from about 1 mol % to about 10 mol % of the polymer. It should also be understood that various other monomeric repeat units can be incorporated into the polymer. For example, in some embodiments, the polymer can include one or more repeat units derived from non-aromatic monomers such as aliphatic or alicyclic hydroxycarboxylic acids, dicarboxylic acids, diols, amides, amines, and the like. Of course, in other embodiments, the polymer can be "fully aromatic" in that it does not include repeat units derived from non-aromatic (e.g., aliphatic or alicyclic) monomers.
[0019]
[0022] Although not required, the liquid crystal polymer may be a "highly naphthenic" polymer, so long as it contains a relatively high content of repeat units derived from naphthenic hydroxycarboxylic acids and naphthenic dicarboxylic acids, such as naphthalene-2,6-dicarboxylic acid (NDA), 6-hydroxy-2-naphthoic acid (HNA), or combinations thereof. That is, the total amount of repeat units derived from naphthenic hydroxycarboxylic acids and / or dicarboxylic acids (e.g., NDA, HNA, or a combination of HNA and NDA) is typically about 10 mol % or more of the polymer, in some embodiments about 15 mol % or more, and in some embodiments about 20 mol % to about 35 mol %. Unlike many conventional "low naphthenic" polymers, it is believed that the resulting "high naphthenic" polymers can exhibit good thermal and mechanical properties. For example, in one particular embodiment, a liquid crystal polymer can be formed from repeat units derived from 4-hydroxybenzoic acid (HBA) and 6-hydroxy-2-naphthoic acid (HNA), as well as various other optional components. The repeat units derived from 4-hydroxybenzoic acid (HBA) can comprise about 50 mol % to about 90 mol %, in some embodiments about 60 mol % to about 85 mol %, and in some embodiments about 65 mol % to about 80 mol % of the polymer. Additionally, the repeating units derived from 6-hydroxy-2-naphthoic acid (HNA) may constitute from about 10 mol % to about 50 mol %, in some embodiments from about 15 mol % to about 40 mol %, and in some embodiments, from about 20 mol % to about 35 mol % of the polymer.
[0020]
[0023] In addition to the liquid crystal polymer, other types of polymers can be used in the polymer matrix, if desired. For example, in one embodiment, the polymer matrix can include aromatic polymers, such as semi-crystalline aromatic polymers (e.g., aromatic and / or semi-crystalline polyamides, polyarylene sulfides, aromatic polyesters, etc.), and / or amorphous polymers (e.g., polyetherimides, polycarbonates, polyphenylene oxides, etc.). When an aromatic polymer is used in combination with a liquid crystal polymer, the liquid crystal polymer typically comprises about 30% to about 85% by weight, in some embodiments about 40% to about 80% by weight, and in some embodiments about 60% to about 75% by weight of the polymer matrix, while the aromatic polymer comprises about 15% to about 70% by weight, in some embodiments about 20% to about 60% by weight, and in some embodiments about 25% to about 40% by weight of the polymer matrix. For example, the aromatic polymer may comprise from about 1% to about 50% by weight, in some embodiments from about 5% to about 45% by weight, and in some embodiments, from about 10% to about 40% by weight of the total polymer composition.
[0021]
[0024] Aromatic polymers are generally considered "high performance" polymers in that they have relatively high glass transition temperatures and / or high melting points depending on the specific properties of the polymer. Thus, such high performance polymers can impart a significant degree of heat resistance to the resulting polymer composition. For example, aromatic polymers can have glass transition temperatures of about 100°C or higher, in some embodiments about 120°C or higher, in some embodiments about 140°C to about 350°C, and in some embodiments about 150°C to about 320°C. Aromatic polymers can also have melting points of about 200°C or higher, in some embodiments about 220°C to about 350°C, and in some embodiments about 240°C to about 300°C. Glass transition temperatures and melting points can be determined using differential scanning calorimetry (DSC), for example, ISO test numbers 11357-2:2013 (glass transition temperature) and 11357-3:2011 (melting point), as is well known in the art.
[0022]
[0025] For example, in one particular embodiment, semi-crystalline aromatic polyesters can be used in the polymer composition. Such aromatic polyesters can be the condensation product of an aromatic dicarboxylic acid having 8 to 14 carbon atoms and at least one diol. Suitable diols include, for example, neopentyl glycol, cyclohexanedimethanol, 2,2-dimethyl-1,3-propanediol, and aryloxycarbonylamine of the formula: HO(CH2) n OH (wherein n is an integer of 2 to 10) can be mentioned. Suitable aromatic dicarboxylic acids include, for example, isophthalic acid, terephthalic acid, 1,2-di(p-carboxyphenyl)ethane, 4,4'-dicarboxydiphenyl ether, etc. and combinations thereof. Also, fused rings may be present, such as in 1,4-, 1,5-, or 2,6-naphthalenedicarboxylic acid. Specific examples of such aromatic polyesters include poly(ethylene terephthalate) (PET), poly(1,4-butylene terephthalate) (PBT), poly(1,3-propylene terephthalate) (PPT), poly(1,4-butylene 2,6-naphthalate) (PBN), poly(ethylene 2,6-naphthalate) (PEN), poly(1,4-cyclohexylene dimethylene terephthalate) (PCT), and copolymers, derivatives, and mixtures of the above.
[0023]
[0026] Additionally, modifications or copolymers of such aromatic polyesters may also be used. For example, in one embodiment, modified acids or diols may be used to produce modified polyethylene terephthalate polymers and / or modified polybutylene terephthalate polymers. The terms "modifying acid" and "modifying diol" as used herein are intended to define compounds that can form part of the acid and diol repeat units of the polyester, respectively, and that can modify the polyester to reduce its crystallinity or render the polyester amorphous. Of course, the polyester may be unmodified and free of modifying acids or diols. In either case, examples of modifying acid components may include, but are not limited to, isophthalic acid, phthalic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, suberic acid, 1,12-dodecanedioic acid, and the like. In practice, it is often preferred to use functional acid derivatives thereof, such as the dimethyl, diethyl, or dipropyl esters of the dicarboxylic acids. The anhydrides or acid halides of these acids can also be used where practical.Examples of modified diol components include neopentyl glycol, 1,4-cyclohexanedimethanol, 1,2-propanediol, 1,3-propanediol, 2-methyl-1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, Z,8-bis(hydroxymethyltricyclo-[5.2.1.0]-decane (wherein Z represents 3, 4, or 5); 1,4-bis(2-hydroxyethoxy)benzene, 4,4' Examples of suitable diols include, but are not limited to, 4,4'-bis(2-hydroxyethoxy)diphenyl ether [bis-hydroxyethyl bisphenol A], 4,4'-bis(2-hydroxyethoxy)diphenyl sulfide [bis-hydroxyethyl bisphenol S], and diols containing one or more oxygen atoms in the chain, such as diethylene glycol, triethylene glycol, dipropylene glycol, tripropylene glycol, and the like. Generally, these diols contain 2 to 18 carbon atoms, and in some embodiments, 2 to 8 carbon atoms. The alicyclic diols can be used in their cis or trans configuration, or as a mixture of both forms.
[0024]
[0027] To help minimize the extent to which the aromatic polyester reacts with the liquid crystal polymer, it is generally desirable to keep the carboxyl end group content in the polymer relatively low, such as about 100 milliequivalents per kilogram (meq / kg) or less, in some embodiments about 50 meq / kg or less, and in some embodiments about 30 meq / kg or less. It is also generally desirable to keep the hydroxyl end group content in the polymer relatively low, such as about 100 meq / kg or less, in some embodiments about 50 meq / kg or less, and in some embodiments about 30 meq / kg or less. The carboxyl and hydroxyl end group content can be determined by any known technique, such as titration (e.g., potentiometry).
[0025] B. Inorganic filler
[0028] As noted above, the polymer composition is a polymeric composition distributed within a polymer matrix. The polymer composition includes one or more inorganic fillers. The inorganic filler or fillers typically comprise about 20 to about 100 parts by weight, in some embodiments about 35 to about 90 parts by weight, and in some embodiments about 50 to about 80 parts by weight, per 100 parts by weight of the polymer matrix. The inorganic filler or fillers may comprise, for example, about 5% by weight to about 60% by weight, in some embodiments about 10% by weight to about 55% by weight, and in some embodiments about 25% by weight to about 40% by weight of the polymer composition.
[0026]
[0029] The nature of the inorganic filler or fillers used in the polymeric composition can vary, such as inorganic particles, inorganic fibers (or whiskers), and the like, as well as blends thereof. Typically, inorganic fillers used in the polymeric composition have a particular hardness value to help improve the mechanical strength, adhesive strength, and surface properties of the composition, thereby making the composition uniquely suitable for forming small parts of a camera module. For example, the hardness value may be about 2.0 or more, in some embodiments about 2.5 or more, in some embodiments about 3.0 or more, in some embodiments about 3.0 to about 11.0, in some embodiments about 3.5 to about 11.0, and in some embodiments about 4.5 to about 6.5, based on the Mohs hardness scale. For example, in some embodiments, the polymeric composition may include a blend of inorganic particles and inorganic fibers. When such blends are used, the inorganic fibers may comprise about 25% to about 70% by weight, in some embodiments about 30% to about 60% by weight, and in some embodiments about 35% to about 50% by weight of the blend, while the inorganic particles may comprise about 30% to about 75% by weight, in some embodiments about 40% to about 70% by weight, and in some embodiments about 50% to about 65% by weight of the blend. The inorganic fibers may comprise, for example, about 1% to about 40% by weight, in some embodiments about 3% to about 25% by weight, and in some embodiments about 5% to about 20% by weight of the total polymer composition, while the inorganic particles may comprise about 2% to about 50% by weight, in some embodiments about 5% to about 40% by weight, in some embodiments about 5% to about 30% by weight, and in some embodiments about 10% to about 30% by weight of the total polymer composition.
[0027]
[0030] In general, any of a variety of different types of inorganic particles can be used in the present polymer compositions, such as those formed from natural and / or synthetic silicate minerals, such as talc, mica, silica (e.g., amorphous silica), alumina, halloysite, kaolinite, illite, montmorillonite, vermiculite, palygorskite, pyrophyllite, calcium silicate, aluminum silicate, wollastonite; sulfates, phosphates, phosphate salts, fluorides, borates, and the like. Calcium carbonate (CaCO3; Mohs hardness 3.0), copper hydroxide carbonate (Cu2CO3(OH)2; Mohs hardness 4.0); calcium fluoride (CaFI2; Mohs hardness 4.0); calcium pyrophosphate (Ca2P2O7; Mohs hardness 5.0), anhydrous dicalcium phosphate (CaHPO4; Mohs hardness 3.5), hydrated aluminum phosphate (AlPO4·2H2O; Mohs hardness 4.5); silica (SiO2; Mohs hardness 5.0-6.0), potassium aluminum silicate Particularly suitable are particles having the desired hardness values, such as carbide (KAlSi3O6; Mohs hardness of 6), copper silicate (CuSiO3·H2O; Mohs hardness of 5.0); calcium borosilicate hydroxide (Ca2B5SiO9(OH)5; Mohs hardness of 3.5); alumina (AlO2; Mohs hardness of 10.0); calcium sulfate (CaSO4; Mohs hardness of 3.5), barium sulfate (BaSO4; Mohs hardness of 3 to 3.5), mica (Mohs hardness of 2.5 to 5.3), and the like, as well as combinations thereof. For example, mica is particularly suitable. In general, moscovite (KAl2(AlSi3)O 10 (OH)2), Biotite (K(Mg,Fe)3(AlSi3)O 10 (OH)2), phlogopite (KMg3(AlSi3)O 10 (OH)2), lepidolite (K(Li,Al) 2~3 (AlSi3)O 10 (OH)2), gluconite (K,Na)(Al,Mg,Fe)2(Si,Al)4O 10 Any form of mica can be used, including moscovite mica. are particularly suitable for use in the present polymer composition.
[0028]
[0031] In some embodiments, inorganic particles such as barium sulfate and / or calcium sulfate particles may have a shape that is generally granular or spherical in nature. In such embodiments, the particles may have a particle size distribution of about 0.5 to 100 nm as determined using laser diffraction techniques (e.g., using a Horiba LA-960 particle size distribution analyzer) in accordance with ISO-13320:2009. The particles may have a median size (e.g., diameter) of about 20 micrometers, in some embodiments, about 1 to about 15 micrometers, in some embodiments, about 1.5 to about 10 micrometers, and in some embodiments, about 2 to about 8 micrometers. In other embodiments, it may be desirable to use flaky inorganic particles, such as mica particles, having a relatively high aspect ratio (e.g., average diameter divided by average thickness), such as about 4 or more, in some embodiments, about 8 or more, and in some embodiments, about 10 to about 500. In such embodiments, the average diameter of the particles may range, for example, from about 5 micrometers to about 200 micrometers, in some embodiments, from about 8 micrometers to about 150 micrometers, and in some embodiments, from about 10 micrometers to about 100 micrometers. The average thickness may also be measured using a laser diffraction (e.g., using a Horiba LA-960 particle size distribution analyzer) according to ISO-13320:2009. The inorganic particles may be about 2 micrometers or less, in some embodiments from about 5 nanometers to about 1 micrometer, and in some embodiments from about 20 nanometers to about 500 nanometers, as determined using folding techniques. The inorganic particles may also have a narrow size distribution, i.e., at least about 70% by volume of the particles, in some embodiments at least about 80% by volume of the particles, and in some embodiments at least about 90% by volume of the particles may have a size within the above ranges.
[0029]
[0032] Suitable inorganic fibers also include those derived from neosilicates, sorosilicates, inosilicates (e.g., calcium inosilicates such as wollastonite; calcium magnesium inosilicates such as tremolite; calcium magnesium iron inosilicates such as actinolite; magnesium iron inosilicates such as anthophillite; etc.), phyllosilicates (e.g., aluminum phyllosilicates such as palygorskite), silicates such as tectosilicates, etc.; sulfates such as calcium sulfate (e.g., dehydrated or anhydrous gypsum); mineral wool (e.g., rock wool or slag wool); and the like. Nyco Minerals offers Nyglos® (e.g., Nyglos® ( Wollastonite (4.5°C), commercially available under the trade names Nyglos® 4W or Nyglos® 8 Particularly suitable are fibers having the desired hardness values, such as inosilicate-derived fibers, such as fibers having a Mohs hardness of 1.0 to 5.0. The inorganic fibers may have a median width (e.g., diameter) of about 1 to about 35 micrometers, in some embodiments about 2 to about 20 micrometers, in some embodiments about 3 to about 15 micrometers, and in some embodiments about 7 to about 12 micrometers. The inorganic fibers may also have a narrow size distribution. That is, at least about 60% by volume of the fibers, in some embodiments at least about 70% by volume of the fibers, and in some embodiments at least about 80% by volume of the fibers may have dimensions within the above ranges. Without intending to be limited by theory, it is believed that inorganic fibers having the above dimensional characteristics may be able to move more easily through a molding apparatus, thereby increasing distribution within the polymer matrix and minimizing the creation of surface defects. In addition to having the above dimensional characteristics, the inorganic fibers may also have a relatively high aspect ratio (average length divided by median width) that helps to further improve the mechanical properties and surface quality of the resulting polymer composition. For example, the inorganic fibers may have an aspect ratio of about 2 to about 100, in some embodiments, about 2 to about 50, in some embodiments, about 3 to about 20, and in some embodiments, about 4 to about 15. The volume average length of such inorganic fibers is, for example, about 1 to about 200 micrometers, in some embodiments, about 2 to about 150 micrometers, and in some embodiments, about 5 to about 100 micrometers. In some embodiments, the diameter may range from about 10 to about 50 micrometers.
[0030] C. Optional Ingredients i. Glass fiber
[0033] One beneficial aspect of the present invention is that good mechanical properties can be achieved without adversely affecting the dimensional stability of the resulting part. To help ensure that this dimensional stability is maintained, it is generally desirable for the polymer composition to remain substantially free of traditional fibrous fillers such as glass fibers. Thus, if used at all, glass fibers typically comprise no more than about 10% by weight of the polymer composition, no more than about 5% by weight in some embodiments, and in some embodiments, from about 0.001% to about 3% by weight.
[0031] ii. Impact modifier
[0034] If desired, impact modifiers can be used in the polymer composition to help improve the impact strength and flexibility of the polymer composition. If used, the impact modifier typically comprises from about 0.1 to about 20 parts by weight, in some embodiments from about 0.5 to about 15 parts, and in some embodiments from about 1 to about 10 parts by weight per 100 parts by weight of the polymer matrix. For example, the impact modifier may comprise from about 0.1% to about 15% by weight, in some embodiments from about 0.2% to about 12% by weight, and in some embodiments from about 0.5% to about 10% by weight of the polymer composition.
[0032]
[0035] For example, in some embodiments, the impact modifier may be a polymer comprising olefinic monomer units derived from one or more α-olefins. Examples of such monomers include, for example, linear and / or branched α-olefins having from 2 to 20 carbon atoms, typically from 2 to 8 carbon atoms. Specific examples include ethylene, propylene, 1-butene; 3-methyl-1-butene; 3,3-dimethyl-1-butene; 1-pentene; 1-pentene with one or more methyl, ethyl, or propyl substituents; 1-hexene with one or more methyl, ethyl, or propyl substituents; 1-heptene with one or more methyl, ethyl, or propyl substituents; 1-octene with one or more methyl, ethyl, or propyl substituents; 1-nonene with one or more methyl, ethyl, or propyl substituents; ethyl, methyl, or dimethyl substituted 1-decene; 1-dodecene; and styrene. Particularly desirable α-olefin monomers are ethylene and propylene. The olefin polymer may be in the form of a copolymer comprising other monomer units known in the art. For example, other suitable monomers can include "(meth)acrylic" monomers, which include acrylic and methacrylic monomers, as well as their salts or esters, such as acrylate and methacrylate monomers. Examples of such (meth)acrylic monomers include methyl acrylate, ethyl acrylate, n-propyl acrylate, i-propyl acrylate, n-butyl acrylate, s-butyl acrylate, i-butyl acrylate, and s-butyl acrylate. Tyl acrylate, t-butyl acrylate, n-amyl acrylate, i-amyl acrylate, isobornyl acrylate, n-hexyl acrylate, 2-ethylbutyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, n-decyl acrylate, methylcyclohexyl acrylate, cyclopentyl acrylate, cyclohexyl acrylate, methyl methacrylate, ethyl methacrylate, 2-hydroxyethyl methacrylate, n-propyl methacrylate, n-butyl methacrylate , i-propyl methacrylate, i-butyl methacrylate, n-amyl methacrylate, n-hexyl methacrylate, i-amyl methacrylate, s-butyl methacrylate, t-butyl methacrylate, 2-ethylbutyl methacrylate, methylcyclohexyl methacrylate, cinnamyl methacrylate, crotyl methacrylate, cyclohexyl methacrylate, cyclopentyl methacrylate, 2-ethoxyethyl methacrylate, isobornyl methacrylate, and combinations thereof. In embodiments, the impact modifier may be an ethylene methacrylic acid copolymer (EMAC). When used, the relative proportions of the monomeric components can be selectively controlled. For example, the α-olefin monomer may comprise from about 55% to about 95% by weight, in some embodiments from about 60% to about 90% by weight, and in some embodiments from about 65% to about 85% by weight of the copolymer. Other monomeric components (e.g., (meth)acrylic monomers) may comprise from about 5% to about 35% by weight, in some embodiments from about 10% to about 32% by weight, and in some embodiments from about 15% to about 30% by weight of the copolymer.
[0033]
[0036] Other suitable olefin copolymers may be "epoxy-functionalized" in that they contain, on average, two or more epoxy functional groups per molecule. The copolymer may also contain epoxy-functional monomer units. One example of such a unit is an epoxy-functional (meth)acrylic monomer component. For example, suitable epoxy-functional (meth)acrylic monomers may include, but are not limited to, those containing 1,2-epoxy groups, such as glycidyl acrylate and glycidyl methacrylate. Other suitable epoxy-functional monomers include allyl glycidyl ether, glycidyl ethyl acrylate, and glycidyl itaconate. Other suitable monomers may also be used to help achieve the desired molecular weight. For example, in one particular embodiment, the copolymer may be a terpolymer formed from an epoxy-functional (meth)acrylic monomer component, an α-olefin monomer component, and a non-epoxy-functional (meth)acrylic monomer component. The copolymer may be, for example, poly(ethylene-co-butyl acrylate-co-glycidyl methacrylate). If used, the one or more epoxy-functional (meth)acrylic monomers typically comprise from about 1% to about 20% by weight, in some embodiments from about 2% to about 15% by weight, and in some embodiments, from about 3% to about 10% by weight of the copolymer.
[0034] iii. Epoxy resin
[0037] In some embodiments, an epoxy resin may also be used, for example, to minimize the extent to which blends of aromatic polymers (e.g., liquid crystalline polymers and semi-crystalline aromatic polyesters) react together during the formation of the polymer composition. If used, the epoxy resin typically comprises from about 0.01 to about 5 parts, in some embodiments from about 0.05 to about 4 parts, and in some embodiments from about 0.1 to about 2 parts, by weight, per 100 parts of the polymer matrix. For example, the epoxy resin may comprise from about 0.01% to about 5% by weight, in some embodiments from about 0.1% to about 4% by weight, and in some embodiments from about 0.3% to about 2% by weight of the polymer composition.
[0035]
[0038] Epoxy resins have a particular epoxy equivalent weight that may be particularly useful for use in polymer compositions. That is, the epoxy equivalent weight is generally about 250 to about 1,500, in some embodiments about 400 to about 1,000, and in some embodiments about 500 to about 800 grams per gram equivalent, as determined according to ASTM-D1652-11e1. Epoxy resins also typically contain, on average, at least about 1.3, in some embodiments about 1.6 to about 8, and in some embodiments about 3 to about 5 epoxide groups per molecule. Epoxy resins also typically have a relatively low kinematic viscosity, such as about 1 to about 25 centipoise, in some embodiments about 2 to about 20 centipoise, and in some embodiments about 5 to about 15 centipoise, as determined according to ASTM-D445-15 at a temperature of 25°C. At room temperature (25°C), epoxy resins are also solid or semi-solid materials that typically have a melting point of from about 50°C to about 120°C, in some embodiments from about 60°C to about 110°C, and in some embodiments, from about 70°C to about 100°C.
[0036]
[0039] The epoxy resin may be saturated or unsaturated, linear or branched, aliphatic, cycloaliphatic, aromatic, or heterocyclic, and may have substituents that do not substantially interfere with the reaction with the oxirane. Suitable epoxy resins include, for example, glycidyl ethers (e.g., diglycidyl ethers) prepared by reacting epichlorohydrin with a hydroxyl compound containing at least 1.5 aromatic hydroxyl groups, optionally under alkaline reaction conditions. Multifunctional compounds are particularly suitable. For example, the epoxy resin may be a diglycidyl ether of a dihydric phenol, a diglycidyl ether of a hydrogenated dihydric phenol, a triglycidyl ether of a trihydric phenol, a triglycidyl ether of a hydrogenated trihydric phenol, etc. The diglycidyl ether of a dihydric phenol may be formed, for example, by reacting epihalohydrin with a dihydric phenol. Examples of suitable dihydric phenols include, for example, 2,2-bis(4-hydroxyphenyl)propane (bisphenol A); 2,2-bis-4-hydroxy-3-tert-butylphenyl)propane; 1,1-bis(4-hydroxyphenyl)ethane; 1,1-bis(4-hydroxyphenyl)isobutane; bis(2-hydroxy-1-naphthyl)methane; 1,5-dihydroxynaphthalene; 1,1-bis(4-hydroxy-3-alkylphenyl)ethane, and the like. Suitable dihydric phenols can also be obtained from the reaction of phenols with aldehydes such as formaldehyde (e.g., bisphenol F). Commercially available examples of such multifunctional epoxy resins include Epon® resins available from Hexion under the names 862, 828, 826, 825, 1001, 1002, 1009, SU3, 154, 1031, 1050, 133, and 165. Other suitable multifunctional epoxy resins are available from Huntsman under the trade name Araldite® (e.g., Araldite® ECN-1273 and Araldite® ECN-1299).
[0037] iv. Antistatic filler
[0040] Antistatic fillers may also be used in the polymeric composition to help reduce the tendency to generate static charges during molding operations, shipping, recovery, assembly, and the like. Such fillers, when used, typically comprise from about 0.1 to about 20 parts by weight, in some embodiments from about 0.2 to about 10 parts, and in some embodiments from about 0.5 to about 5 parts, per 100 parts by weight of the polymeric matrix. For example, the antistatic filler may comprise from about 0.1% to about 10% by weight, in some embodiments from about 0.2% to about 8% by weight, and in some embodiments from about 0.5% to about 4% by weight of the polymeric composition.
[0038]
[0041] Any of a variety of antistatic fillers can generally be used in the polymer composition to help improve its antistatic properties. Examples of suitable antistatic fillers can include, for example, metal particles (e.g., aluminum flakes), metal fibers, carbon particles (e.g., graphite, expanded graphite, graphite, graphene, carbon black, graphitized carbon black, etc.), carbon nanotubes, carbon fibers, and the like. For example, in one embodiment, the antistatic filler can be an ionic liquid. One advantage of such materials is that, in addition to being antistatic agents, ionic liquids can also exist in liquid form during melt processing, which allows them to be more uniformly blended within the polymer matrix. This improves electrical connectivity, thereby enhancing the ability of the composition to quickly dissipate static charge from its surface. Ionic liquids are generally salts that have a melting temperature low enough to allow them to be in liquid form when melt processed with the liquid crystal polymer. For example, the melting temperature of the ionic liquid can be about 400° C. or less, in some embodiments about 350° C. or less, in some embodiments about 1° C. to about 100° C., and in some embodiments about 5° C. to about 50° C. Salts include cationic species and counterions. Cationic species include compounds having at least one heteroatom (e.g., nitrogen or phosphorus) as the "cationic center." Examples of such heteroatom compounds include those having the following structures:
[0039] [ka]
[0040] (In the formula, R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , and R 8 are independently hydrogen; substituted or unsubstituted C1-C 10 Alkyl groups (e.g., methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, etc.); substituted or unsubstituted C3-C 14 Cycloalkyl groups (e.g., adamantyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclooctyl, cyclohexenyl, etc.); substituted or unsubstituted C1-C 10 Alkenyl groups (e.g., ethylene, propylene, 2-methylpropylene, pentylene, etc.); substituted or unsubstituted C2-C 10 Alkynyl groups (e.g., ethynyl, propynyl, etc.); substituted or unsubstituted C1-C 10 Included are quaternary oniums having alkoxy groups (e.g., methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, t-butoxy, sec-butoxy, n-pentoxy, etc.); substituted or unsubstituted acyloxy groups (e.g., methacryloxy, methacryloxyethyl, etc.); substituted or unsubstituted aryl groups (e.g., phenyl); substituted or unsubstituted heteroaryl groups (e.g., pyridyl, furanyl, thienyl, thiazolyl, isothiazolyl, triazolyl, imidazolyl, isoxazolyl, pyrrolyl, pyrazolyl, pyridazinyl, pyrimidinyl, quinolyl, etc.); and the like. For example, in one particular embodiment, the cationic species is selected from the group consisting of: + R 1 R 2 R 3 R 4 (In the formula, R 1 , R 2 , and / or R 3 are independently C1-C6 alkyl (e.g., methyl, ethyl, butyl, etc.), and R 4is an ammonium compound having hydrogen or a C1-C4 alkyl group (e.g., methyl or ethyl). For example, the cationic component may be tributylmethylammonium (R 1 , R 2 , and R 3 is butyl, and R 4 is methyl).
[0041]
[0042] Suitable counterions for the cationic species include, for example, halogens (e.g., chlorine, bromine, iodine, etc.); sulfates or sulfonates (e.g., methyl sulfate, ethyl sulfate, butyl sulfate, hexyl sulfate, octyl sulfate, hydrogen sulfate, methanesulfonate, dodecylbenzenesulfonate, dodecyl sulfate, trifluoromethanesulfonate, heptadecafluorooctanesulfonate, sodium dodecylethoxysulfate, etc.); sulfosuccinates; amides (e.g., dicyanamide); imides (e.g., bis(pentafluoroethyl-sulfonyl)imide, bis(trifluoromethylsulfonyl)imide, bis(trifluoromethyl)imide, etc.); borates (e.g., tetrafluoroethylene ... Fluoroborate, tetracyanoborate, bis[oxalato]borate, bis[salicylate]borate, etc.); phosphate or phosphinate (e.g., hexafluorophosphate, diethylphosphate, bis(pentafluoroethyl)phosphinate, tris(pentafluoroethyl)trifluorophosphate, tris(nonafluorobutyl)trifluorophosphate, etc.); antimonate (e.g., hexafluoroantimonate); aluminate (e.g., tetrachloroaluminate); fatty acid carboxylate (e.g., oleate, isostearate, pentadecafluorooctanoate, etc.); cyanate; acetate; and the like, as well as combinations of any of the above. To help improve compatibility with the liquid crystal polymer, it may be desirable to select counterions that are generally hydrophobic in nature, such as imides, fatty acid carboxylates, and the like. Particularly suitable hydrophobic counterions can include, for example, bis(pentafluoroethylsulfonyl)imide, bis(trifluoromethylsulfonyl)imide, and bis(trifluoromethyl)imide.
[0042] v. Tribological formulation
[0043] Tribological agents may also be used in the polymeric composition, typically in an amount of from about 1 to about 30 parts, in some embodiments from about 2 to about 15 parts, and in some embodiments from about 4 to about 12 parts per 100 parts of the aromatic polymer(s) used in the polymeric composition. For example, the tribological agent may comprise from about 1% to about 30% by weight, in some embodiments from about 2% to about 25% by weight, and in some embodiments from about 4% to about 10% by weight of the polymeric composition.
[0043]
[0044] The tribological agent may include a siloxane polymer, which also serves to improve internal lubricity and enhance the wear and friction properties of the composition in contact with other surfaces. Such siloxane polymers typically comprise from about 0.1 to about 20 parts, in some embodiments from about 0.4 to about 10 parts, and in some embodiments from about 0.5 to about 5 parts per 100 parts of the aromatic polymer or polymers used in the composition. Any of a variety of siloxane polymers may be used in the tribological agent. Siloxane polymers may, for example, comprise a siloxane having a structure of the formula: R r SiO (4-r / 2) (In the formula, R is independently hydrogen or a substituted or unsubstituted hydrocarbon group; r is 0, 1, 2, or 3. The present invention may include any polymer, copolymer, or oligomer that includes siloxane units having the formula:
[0044]
[0045] Some examples of suitable groups R include, for example, optionally substituted alkyl, aryl, alkylaryl, alkenyl, or alkynyl, or cycloalkyl groups, which may be interrupted by heteroatoms, i.e., one or more heteroatoms in the carbon chain or ring. Suitable alkyl groups may include, for example, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, and tert-pentyl groups, hexyl groups (e.g., n-hexyl), heptyl groups (e.g., n-heptyl), octyl groups (e.g., n-octyl), isooctyl groups (e.g., 2,2,4-trimethylpentyl), nonyl groups (e.g., n-nonyl), decyl groups (e.g., n-decyl), dodecyl groups (e.g., n-dodecyl), and octadecyl groups (e.g., n-octadecyl). Suitable cycloalkyl groups include cyclopentyl, cyclohexyl, cycloheptyl, methylcyclohexyl, etc.; suitable aryl groups include phenyl, biphenyl, naphthyl, anthryl, and phenanthryl; suitable alkylaryl groups include o-, m-, or p-tolyl, xylyl, ethylphenyl, etc.; suitable alkenyl or alkynyl groups include vinyl, 1-propenyl, 1-butenyl, 1-pentenyl, 5-hexenyl, butadienyl, hexadienyl, cyclopentenyl, cyclopentadienyl, cyclohexenyl, ethynyl, propargyl, 1-propynyl, etc. Examples of substituted hydrocarbon groups include halogenated alkyl groups (e.g., 3-chloropropyl, 3,3,3-trifluoropropyl, and perfluorohexylethyl), and halogenated aryl groups (e.g., p-chlorophenyl, and p-chlorobenzyl). In one particular embodiment, the siloxane polymer comprises alkyl groups (e.g., methyl groups) attached to at least 70 mol % of the Si atoms, and optionally vinyl and / or phenyl groups attached to 0.001-30 mol % of the Si atoms. The siloxane polymer is also preferably composed mainly of diorganosiloxane units. The terminal groups of the polyorganosiloxane may be trialkylsiloxy groups, in particular trimethylsiloxy groups, or dimethylvinylsiloxy groups. However, one or more of these alkyl groups may be substituted with hydroxy groups or alkoxy groups, such as methoxy or ethoxy groups.Particularly suitable examples of siloxane polymers include, for example, dimethylpolysiloxane, phenylmethylpolysiloxane, vinylmethylpolysiloxane, and trifluoropropylpolysiloxane.
[0045]
[0046] The siloxane polymers may also contain, on at least a portion of the siloxane monomer units of the polymer, vinyl groups, hydroxyl groups, hydrides, isocyanate groups, epoxy groups, acid groups, halogen atoms, alkoxy groups (e.g., methoxy, ethoxy, and propoxy), acyloxy groups (e.g., acetoxy, and octanoyloxy), ketoximate groups (e.g., dimethylketoxime, methylketoxime, and methylethylketoxime), amino groups (e.g., dimethylamino, diethylamino, and butylamino), aryl groups (e.g., aryloxy ... The aryloxy groups may contain reactive functional groups such as one or more of amide groups (e.g., N-methylacetamide, and N-ethylacetamide), acid amide groups, amino-oxy groups, mercapto groups, alkenyloxy groups (e.g., vinyloxy, isopropenyloxy, and 1-ethyl-2-methylvinyloxy), alkoxyalkoxy groups (e.g., methoxyethoxy, ethoxyethoxy, and methoxypropoxy), aminooxy groups (e.g., dimethylaminooxy, and diethylaminooxy), mercapto groups, and the like.
[0046]
[0047] Regardless of its specific structure, the siloxane polymer may have a relatively high molecular weight, which reduces its tendency to migrate or diffuse to the surface of the polymer composition, thus further minimizing the possibility of phase separation.For example, the siloxane polymer typically has a weight average molecular weight of about 100,000 grams / mole or more, in some embodiments about 200,000 grams / mole or more, and in some embodiments about 500,000 grams / mole to about 2,000,000 grams / mole.The siloxane polymer may also have a relatively high kinematic viscosity, such as about 10,000 centistokes or more, in some embodiments about 30,000 centistokes or more, and in some embodiments about 50,000 to about 500,000 centistokes.
[0047]
[0048] If desired, silica particles (e.g., fumed silica) can also be used in combination with the siloxane polymer to help improve its ability to disperse in the composition. Such silica particles can have, for example, a particle size of about 5 nanometers to about 50 nanometers, a particle size of about 50 square meters per gram (m 2 / g) ~ approx. 600m 2 / g surface area, and / or approximately 160 kilograms per cubic meter (kg / m 3 ) ~ approx. 190kg / m 3 The silica particles may have a density of about 100 to about 100 parts by weight, and in some embodiments about 20 to about 60 parts by weight, based on 100 parts by weight of the siloxane polymer. In one embodiment, the silica particles can be mixed with the siloxane polymer before the mixture is added to the polymer composition. For example, a mixture containing ultra-high molecular weight polydimethylsiloxane and fumed silica can be introduced into the polymer composition. Such preformed mixtures are available as Genioplast® pellets S from Wacker Chemie, AG.
[0048]
[0049] The tribological agent may also include other components that may help the resulting polymeric composition achieve a good combination of low friction and good wear resistance. For example, in one embodiment, the tribological agent may use a fluorinated additive in combination with a siloxane polymer. Without intending to be limited by theory, it is believed that the fluorinated additive may improve the processability of the composition, such as by providing better mold filling, internal lubrication, mold release, among others. When used, the weight ratio of the fluorinated additive to the siloxane polymer is typically about 0.5 to about 12, in some embodiments about 0.8 to about 10, and in some embodiments about 1 to about 6. For example, the fluorinated additive may comprise about 0.1 to about 20 parts, in some embodiments about 0.5 to about 15 parts, and in some embodiments about 1 to about 10 parts per 100 parts of the aromatic polymer or polymers used in the composition.
[0049]
[0050] In certain embodiments, the fluorinated additive can include a fluoropolymer that includes a hydrocarbon backbone polymer in which some or all of the hydrogen atoms are replaced with fluorine atoms. The backbone polymer can be polyolefinic and can be formed from fluorine-substituted unsaturated olefin monomers. The fluoropolymer can be a homopolymer of such fluorine-substituted monomers, or a copolymer of fluorine-substituted monomers, or a mixture of fluorine-substituted and non-fluorine-substituted monomers. In addition to fluorine atoms, the fluoropolymer can be substituted with other halogen atoms, such as chlorine and bromine atoms. Representative monomers suitable for forming fluoropolymers for use in the present invention are tetrafluoroethylene, vinylidene fluoride, hexafluoropropylene, chlorotrifluoroethylene, perfluoroethyl vinyl ether, perfluoromethyl vinyl ether, perfluoropropyl vinyl ether, and the like, and mixtures thereof. Specific examples of suitable fluoropolymers include polytetrafluoroethylene, perfluoroalkyl vinyl ethers, poly(tetrafluoroethylene-co-perfluoroalkyl vinyl ethers), fluorinated ethylene-propylene copolymers, ethylene-tetrafluoroethylene copolymers, polyvinylidene fluoride, polychlorotrifluoroethylene, and the like, as well as mixtures thereof.
[0050]
[0051] The fluorinated additive may include only the fluoropolymer, or may include other components, such as those that aid in its ability to disperse uniformly within the polymer composition. For example, in one embodiment, the fluorinated additive may include a fluoropolymer in combination with a plurality of carrier particles. For example, in such an embodiment, the fluoropolymer may be coated onto the carrier particles. Talc (Mg3SiO4O 10 (OH)2), halloysite (Al2Si2O5(OH)4), kaolinite (Al2Si2O5(OH)4), illite ((K,H3O)(Al,Mg,Fe)2(Si,Al)4O 10 [ (OH)2,(H2O)], Montmorillonite (Na,Ca) 0.33 (Al,Mg)2Si4O 10 (OH)2·nH2O), vermiculite ((MgFe,Al)3(Al,Si)4O 10 (OH)2·4H2O), palygorskite ((Mg,Al)2Si4O 10 (OH)·4(H2O)), pyrophyllite (Al2Si4O 10 Particularly suitable for this purpose are silicate particles such as moscovite (KA12(AlSi3)O4), calcium silicate, aluminum silicate, mica, diatomaceous earth, wollastonite, and the like. For example, mica may be a particularly suitable mineral for use in the present invention. There are several chemically distinct mica species with significant differences in their geological existence, but all have substantially the same crystal structure. As used herein, the term "mica" refers to moscovite (KA12(AlSi3)O4), calcium silicate, aluminum silicate, mica, diatomaceous earth, wollastonite, and the like. 10 (OH)2), Biotite (K(Mg,Fe)3(AlSi3)O 10 (OH)2), phlogopite (KMg3(AlSi3)O 10 (OH)2), lepidolite (K(Li,Al) 2~3 (AlSi3)O 10 (OH)2), gluconite (K,Na)(Al,Mg,Fe)2(Si,Al)4O 10 (OH)2), and the like, as well as combinations thereof. The carrier particles may have an average particle size of about 5 to about 50 micrometers, and in some embodiments, about 10 to 20 micrometers. If desired, the carrier particles may also be in the shape of plate-like particles, in that the ratio of their major axis to thickness is 2 or greater.
[0051] vi. Other additives
[0052] A wide range of additional additives can also be included in the polymer composition, such as lubricants, thermally conductive fillers, pigments, antioxidants, stabilizers, surfactants, waxes, flame retardants, anti-sag additives, nucleating agents (e.g., boron nitride), and other materials added to enhance properties and processability. For example, lubricants that can withstand the processing conditions of liquid crystal polymers without substantial decomposition can be used in the polymer composition. Examples of such lubricants include fatty acid esters, their salts, esters, fatty acid amides, organic phosphate esters, and hydrocarbon waxes of the type commonly used as lubricants in the processing of engineering plastic materials, and mixtures thereof. Suitable fatty acids typically have a backbone carbon chain of about 12 to about 60 carbon atoms, such as myristic acid, palmitic acid, stearic acid, arachidic acid, montanic acid, octadecanoic acid, parinaric acid, and the like. Suitable esters include fatty acid esters, fatty alcohol esters, wax esters, glycerol esters, glycol esters, and complex esters. Fatty acid amides include fatty acid primary amides, fatty acid secondary amides, methylene and ethylene bisamides, and alkanolamides, such as palmitic acid amide, stearic acid amide, oleic acid amide, N,N'-ethylene bisstearamide, and the like. Also suitable are metal salts of fatty acids, such as calcium stearate, zinc stearate, magnesium stearate, and the like; and hydrocarbon waxes, such as paraffin wax, polyolefin and oxidized polyolefin waxes, and microcrystalline waxes. Particularly suitable lubricants are stearic acid, salts, or amides, such as pentaerythritol tetrastearate, calcium stearate, or N,N'-ethylene bisstearamide. When used, the lubricant or lubricants typically comprise from about 0.05% to about 1.5% by weight, and in some embodiments, from about 0.1% to about 0.5% by weight (by weight) of the polymer composition.
[0052] II. Formation
[0053] The components of the polymer composition (e.g., one or more liquid crystalline polymers, one or more inorganic fillers, etc.) can be melt processed or blended together. The components can be fed separately or in combination to an extruder that includes at least one screw rotatably mounted within and contained within a barrel (e.g., a cylindrical barrel) and defines a feed section along the length of the screw and a melt section located downstream from the feed section. The extruder can be a single or twin screw extruder. The screw speed can be selected to achieve the desired residence time, shear rate, melt processing temperature, etc. For example, the screw speed may range from about 50 to about 800 revolutions per minute (rpm), in some embodiments from about 70 to about 150 rpm, and in some embodiments from about 80 to about 120 rpm. Also, the apparent shear rate during melt blending is about 100 s -1 ~about 10,000 seconds -1 , in some embodiments, about 500 seconds -1 ~about 5000 seconds -1 , in some embodiments, about 800 seconds -1 ~about 1200 seconds -1 The apparent shear rate can be in the range of 4Q / πR 3 (where Q is the volumetric flow rate of the polymer melt (m 3 / sec), where R is the radius (m) of the capillary (e.g., extruder die) through which the molten polymer flows.
[0053] III. Camera Module
[0054] As indicated above, the polymer composition of the present invention can be used in a camera module. Typically, a camera module includes a housing in which a lens module containing one or more lenses is disposed. However, the specific structure of the camera module can be modified as known to those skilled in the art.
[0054]
[0055] For example, referring to FIG. 1 , an embodiment of a camera module 100 is shown that includes a lens module 120 contained within a housing, the lens module 120 including a lens barrel 121 coupled to a lens holder 123. The lens barrel 121 may have a hollow cylindrical shape such that a plurality of lenses for imaging an object can be accommodated therein in an optical axis direction 1. The lens barrel 121 is inserted into a hollow cavity provided within the lens holder 123, and the lens barrel 121 and the lens holder 123 can be coupled to each other by fasteners (e.g., screws), adhesives, and the like. The lens module 120 including the lens barrel 121 may be movable in the optical axis direction 1 (e.g., for autofocus) by an actuator assembly 150. For example, in the embodiment shown, the actuator assembly 150 may include a magnetic body 151 and a coil 153 configured to move the lens module 120 in the optical axis direction 1. The magnetic body 151 may be mounted on one side of the lens holder 123, and the coil 153 may be positioned to face the magnetic body 151. The coil 153 can be mounted on a substrate 155, which can then be attached to the housing 130 such that the coil 153 faces the magnetic material 151. The actuator assembly 150 can include a driver 160 mounted on the substrate 155 and configured to output a signal (e.g., a current) for driving the actuator assembly 150 in response to a control input signal. The actuator assembly 150 can receive the signal and generate a driving force to move the lens module 120 in the optical axis direction 1. If desired, a stopper 140 can also be attached on the housing 130 to limit the distance of movement of the lens module 120 in the optical axis direction 1. Additionally, a shielding case 110 (e.g., metal) can be coupled to the housing 130 to encapsulate the outer surface of the housing 130, thereby blocking electromagnetic waves generated during operation of the camera module 100.
[0055]
[0056] The actuator assembly may also include a guide unit disposed between the housing and the lens module to help guide the movement of the lens module. Any of a variety of guide units known in the art may be used, such as one or more springs, one or more ball bearings, an electrostatic force generator, a hydraulic force generator, and the like. For example, a spring may be used that creates a preload that acts on the lens module to guide it in the desired optical axis direction. Alternatively, as shown in the embodiment shown in FIG. 1, a ball bearing 170 may function as a guide unit for the actuator assembly 150. More specifically, the ball bearing 170 may be in contact with an outer surface of the lens holder 123 and an inner surface of the housing 130 to guide the lens module 1 in the desired optical axis direction. The ball bearing 170 can guide the movement of the lens module 120 in the optical axis direction 1. That is, the ball bearing 170 can be disposed between the lens holder 123 and the housing 130, and can guide the movement of the lens module 120 in the optical axis direction 1 by rolling. For this purpose, any number of ball bearings 170 can be used, generally 2 or more, in some embodiments 3 to 20, in some embodiments 4 to 12. The ball bearings 170 can be gapped or in contact with each other, and can also be stacked in a direction perpendicular to the optical axis direction 1. The dimensions of the ball bearings 170 can be varied as known to those skilled in the art. For example, the ball bearings can have an average dimension (e.g., diameter) of about 800 micrometers or less, in some embodiments about 600 micrometers or less, in some embodiments about 400 micrometers or less, and in some embodiments about 50 to about 200 micrometers.
[0056]
[0057] In particular, the polymer composition of the present invention can be used in any of the various components of a camera module. For example, referring again to FIG. 1, the polymer composition can be used to form all or part of the guide unit (e.g., ball bearing 170), housing 130, lens barrel 121, lens holder 123, substrate 155, stopper 140, shield case 110, and / or any other part of the camera module. Regardless, one or more desired components can be formed using a variety of different techniques. Suitable techniques can include, for example, injection molding, low pressure injection molding, extrusion compression molding, gas injection molding, foam injection molding, low pressure gas injection molding, low pressure foam injection molding, gas extrusion compression molding, foam extrusion compression molding, extrusion molding, foam extrusion molding, compression molding, foam compression molding, gas compression molding, and the like. For example, an injection molding system can be used that includes a mold into which the polymer composition can be injected. The time inside the injector can be controlled and optimized to prevent the polymer matrix from prematurely solidifying. When the cycle time is reached and the barrel is full for discharge, the composition can be injected into the mold cavity using a piston. Compression molding systems can also be used. Similar to injection molding, the molding of the polymer composition into the desired article is also performed in a mold. The composition can be placed into the compression mold using any known technique, for example by picking up by an automated robotic arm. The temperature of the mold can be maintained above the solidification temperature of the polymer matrix for a desired time to allow solidification. The molded article can then be solidified by bringing it below its melting point. The resulting product can be demolded. The cycle time for each molding process can be adjusted to match the polymer matrix, achieve sufficient bonding, and increase the productivity of the overall process.
[0057]
[0058] The resulting camera module can be used in a wide range of electronic devices known in the art, such as portable electronic devices (e.g., cell phones, portable computers, tablets, watches, etc.), computers, televisions, automotive parts, etc. In one particular embodiment, the polymer composition can be used in a camera module such as those commonly used in wireless communication devices (e.g., cell phones). For example, with reference to FIGS. 2-3, an embodiment of an electronic device 2 (e.g., a phone) is shown that includes a camera module 100. As shown, the lens of the camera module 100 can be exposed to the exterior of the electronic device 2 through an opening 2b to image an external object. The camera module 100 can also be electrically connected to an application specific integrated circuit 2c to perform control operations as selected by a user. EXAMPLES
[0058]
[0059] The invention can be better understood with reference to the following examples. Test Method
[0060] Friction and wear: SSP-03 machine, VDA-230-206:2007 (steer The degree of friction generated by the specimen can be characterized by the average dynamic friction coefficient (dimensionless) determined according to the VDA-230-206:2007 (Dynamic Slip Test). The degree of wear of the test specimen can also be determined according to VDA-230-206:2007. More specifically, the polymer product is used to prepare ball-shaped and plate-shaped specimens by an injection molding process. The ball specimens are 0.5 inches in diameter. The plate specimens are obtained from the center of an ISO tensile bar by cutting the two end regions of the tensile bar. The plate specimen is fixed on a specimen holder and the ball specimen is moved in contact with the plate specimen at 150 mm / s and a force of 15 N. After 1000 cycles, the dynamic friction coefficient is obtained. The wear depth is obtained from the ball specimen by measuring the diameter of the worn ball area. Based on the diameter of the worn area, the wear depth of the ball specimen is calculated.
[0059]
[0061] Melt Viscosity: Melt viscosity (Pa·sec) was measured at 400 s using a Dynisco LCR 7001 capillary flowmeter according to ISO test No. 11443:2005. -1 and a temperature 15° C. above the melting point (e.g., 305° C.). The flowmeter orifice (die) had a diameter of 1 mm, a length of 20 mm, an L / D ratio of 20.1, and an entrance angle of 180°. The barrel diameter was 9.55 mm+0.005 mm and the rod length was 233.4 mm.
[0060]
[0062] Melting point: Melting point (Tm) can be determined by differential scanning calorimetry (DSC) as known in the art. Melting point is the differential scanning calorimetry (DSC) peak melting temperature as determined by ISO test No. 11357-2:2013. In the DSC procedure, samples were heated and cooled at 20°C / min as specified in ISO standard 10350 with DSC measurements performed on a TA-Q2000 instrument.
[0061]
[0063] Deflection Temperature Under Load (DTUL): Deflection temperature under load can be determined according to ISO Test No. 75-2:2013 (technically equivalent to ASTM-D648-07). More specifically, a test specimen sample having a length of 80 mm, a thickness of 10 mm, and a width of 4 mm can be subjected to a 3-point longitudinal bending test with a prescribed load (maximum outer fiber stress) of 1.8 megapascals. The test specimen can be lowered into a silicone oil bath where the temperature is increased at 2°C / min until it is deflected 0.25 mm (0.32 mm for ISO Test No. 75-2:2013).
[0062]
[0064] Tensile modulus, tensile stress, and tensile elongation: Tensile properties can be tested according to ISO Test No. 527:2012 (technically equivalent to ASTM-D638-14). Modulus and strength measurements can be performed on the same test specimen sample with a length of 80 mm, a thickness of 10 mm, and a width of 4 mm. The test temperature can be 23°C, and the test speed can be 1 or 5 mm / min.
[0063]
[0065] Flexural modulus, flexural stress, and flexural elongation: Flexural properties can be tested according to ISO Test No. 178:2010 (technically equivalent to ASTM-D790-10). The test can be performed on a support span of 64 mm. The test can be performed on the center section of an uncut ISO-3167 multipurpose bar. The test temperature can be 23° C. and the test speed can be 2 mm / min.
[0064]
[0066] Unnotched and notched Charpy impact strength: Charpy properties can be tested according to ISO Test No. 179-1:2010 (technically equivalent to ASTM-D256-10, Method B). This test can be performed using Type 1 specimen dimensions (80 mm length, 10 mm width, and 4 mm thickness). When testing notched impact strength, the notch can be a Type A notch (0.25 mm base radius). Specimens can be cut from the center of the general purpose bar using a single tooth milling machine. The test temperature may be 23°C.
[0065]
[0067] Rockwell Hardness: Rockwell hardness is a measure of the indentation resistance of a material and can be determined according to ASTM-D785-08 (scale M). The test is performed by first pressing a steel ball indenter into the surface of the material with a specified small load. The load is then increased to a specified large load and decreased back to the original small load. Rockwell hardness is a measure of the net increase in indenter depth and is calculated by subtracting 130 from the amount of penetration divided by the scale division.
[0066]
[0068] Surface / Volume Resistivity: Surface and volume resistivity values are generally determined according to IEC-60093 (equivalent to ASTM-D257-07). According to this procedure, a standard test piece (e.g., 1 meter cubed) is placed between two electrodes. A voltage is applied for 60 seconds and the resistance is measured. Surface resistivity is the quotient of the potential gradient (V / m) and the current per unit electrode length (A / m), and generally represents the resistance to leakage current along the surface of an insulating material. Since the four edges of the electrode define a square, the length is reduced in the quotient and surface resistivity is reported in Ω, although it is common to see the more descriptive unit of Ω / square. Volume resistivity is also determined as the ratio of the potential gradient parallel to the current in the material to the current density. In SI units, volume resistivity is numerically equal to the DC resistance between the opposing faces of a 1 meter cube of material (Ω·m).
[0067]
[0069] Ball Indentation Test: A "ball indentation" test can be performed to test the ability of a material to withstand physical forces. More specifically, a sample composition can be injection molded into a test specimen with a width and length of 40 mm and a thickness of 2 mm. Other thicknesses such as 0.2 mm can also be tested. Once formed, a metal ball (1.5 mm in diameter) can be dropped once from a distance of 10 cm or 15 cm from the top surface of the test specimen. Various ball weights such as 35 grams, 50 grams, and 75 grams can be tested. After the ball contacts the test specimen, a Keyence image measurement sensor is used to measure the indentation formed in the test specimen. The depth and diameter of the dent shall be measured.
[0068]
[0070] Mini-Drop Test: Another technique for testing the ability of materials to withstand physical forces is the "mini-drop" test. More specifically, a sample composition can be injection molded into a test specimen having a width and length of 40 mm and a thickness of 2 mm. Other thicknesses such as 0.2 mm can also be tested. Once formed, a metal ball (1.5 mm diameter, 5 grams) can be dropped multiple times (e.g., 10,000 or 20,000 times) from a distance of 150 mm onto the top surface of the test specimen. The test specimen is then imaged using a Keyence image measurement sensor. The depth (in micrometers) of the indentation formed in the specimen is measured.
[0069] Example 1
[0071] The mixture was made of various proportions of liquid crystal polymer (LCP), polycyclohexylene dimethylene terephthalate (PCT), wollastonite fiber (Nyglos® 4W), mica (C-4000), talc (Flextalc® 815), ethylene methacrylic acid copolymer (EMAC® SP-2260), boron nitride, a first epoxy resin (Araldite® ECN-1299, epoxy resin). Epoxy resin 1), a second epoxy resin (Epon® 1009F, epoxy resin 2), black pigment, lubricant (Licowax® PED-521), and various antioxidant stabilizers (AO-1010 and AO-126). Samples 1 to 5 are formed from the above. The PCT polymer has an intrinsic viscosity of 0.62. In sample 2, an LCP polymer (LCP-1) is formed from 79.3 mol% HBA, 20 mol% HNA, and 0.7 mol% TA (Tm=325°C). In sample 3, an LCP polymer (LCP-2) is formed from 73 mol% HBA and 27 mol% HNA (Tm=280°C). In sample 4, an LCP polymer (LCP-3) is formed from 60 mol% HBA, 4.25 mol% HNA, 17.875 mol% BP, and 17.875 mol% TA (Tm=325°C). % HBA, 8.57 mol % TA, 28.57 mol % HQ, and 20 mol % NDA (Tm=360° C.). Finally, in sample 5. LCP polymer (LCP-4) is formed from 42.86 mol % HBA, 8.57 mol % TA, 28.57 mol % HQ, and 20 mol % NDA (Tm=300° C.). Compounding was performed using an 18 mm single screw extruder. Samples were injection molded into plaques (60 mm×60 mm) to form parts.
[0070] [Table 1]
[0071]
[0072] Samples 1-5 were tested for thermal and mechanical properties and the results are shown in Table 2 below.
[0072] [Table 2]
[0073] Example 2
[0073] Various proportions of the above-described LCP-2, polycyclohexylene dimethylene terephthalate (PCT), wollastonite fiber (Nyglos® 4W), mica (C-4000), talc (Flextalc® 815), ethylene methacrylic acid copolymer (EMAC® SP-2260), boron nitride, a first epoxy resin (Araldite® ECN-1299, epoxy resin 1), a second epoxy resin (Epon® 1009F, epoxy resin 2), a black pigment, Samples 6-9 are formed from a PCT polymer with a 0.62 intrinsic viscosity. Compounding was performed using an 18 mm single screw extruder. Samples are injection molded into plaques (60 mm x 60 mm) to form parts.
[0074] [Table 3]
[0075]
[0074] Samples 7-8 were tested for mechanical properties, and the results are shown in Table 4 below.
[0076] [Table 4]
[0077] Example 3
[0075] Various proportions of liquid crystal polymer (LCP-1, LCP-2, LCP-3, or LCP-4 as described above), polycyclohexylene dimethylene terephthalate (PCT), wollastonite fiber (Nyglos® 4W), mica (C-4000), talc (Flextalc® 815), ethylene methacrylic acid copolymer (EMAC® SP-2260), boron nitride, a first The epoxy resin (Araldite® ECN-1299, epoxy resin 1), a second epoxy resin (Epon® 1009F, epoxy resin 2), a black pigment, a lubricant (Licowax™ PED-521), an ionic liquid (FC-4400), and various antioxidant stabilizers (AO-1010 and AO-126) were used as the test materials. Compounds 10-13 are formed. The PCT polymer has an intrinsic viscosity of 0.62. Compounding was performed using an 18 mm single screw extruder. Samples are injection molded into plaques (60 mm x 60 mm) to form parts.
[0078] [Table 5]
[0079]
[0076] Samples 10-13 were tested for mechanical properties, and the results are shown in Table 6 below.
[0080] [Table 6]
[0081] Example 4 Samples 14-16 are formed from various proportions of liquid crystal polymer (LCP-1 and LCP-2 described above), wollastonite fiber (Nyglos® 4W), mica, ethylene / n-butyl acrylate / glycidyl methacrylate terpolymer (Elvaloy® PTW), ultra-high molecular weight siloxane polymer (Genioplast® pellets S), polyethylene, and / or ionic liquid (FC-4400). The samples are injection molded into plaques (60 mm x 60 mm). to form the part.
[0082] [Table 7]
[0083]
[0078] Samples 14-16 were tested for mechanical properties and the results are shown in Table 8 below.
[0084] [Table 8]
[0085] Example 5 Samples 17-20 were formed from various proportions of liquid crystal polymer (LCP-1 and LCP-2 described above), wollastonite fiber (Nyglos® 4W), barium sulfate, ethylene / n-butyl acrylate / glycidyl methacrylate terpolymer (Elvaloy® PTW), and / or ionic liquid (FC-4400). The samples were applied to plaques (60 mm×60 mm). The part is formed by injection molding.
[0086] [Table 9]
[0087]
[0080] Samples 17-20 were tested for mechanical properties and the results are shown in Table 10 below.
[0088] [Table 10]
[0089] Example 6
[0081] Various proportions of liquid crystal polymers (LCP-1 and LCP-2 described above), wollastonite fiber (Nyglos® 4W), anhydrous barium sulfate, ionic liquid (FC-4400), and black pigment were mixed. The material is used to form samples 21 to 22. The samples are injection molded into plaques (60 mm x 60 mm) to form parts.
[0090] [Table 11]
[0091]
[0082] Samples 21-22 were tested for mechanical properties and the results are shown in Table 12 below.
[0092] [Table 12]
[0093] Example 7 Samples 23-26 were formed from various proportions of liquid crystal polymer (LCP-1 and LCP-2 described above), and samples 24-26 were formed from various proportions of liquid crystal polymer (LCP-1 and LCP-2 described above), wollastonite fiber (Nyglos® 4W), amorphous silica (1.7 μm median particle size), terpolymer of ethylene, acrylate, and glycidyl methacrylate (Lotarder® AX8900), ultra-high molecular weight siloxane polymer (Genioplast® pellets S), polytetrafluoroethylene (PTFE), calcium sulfate, and mica. Form samples 14 to 16. Injection mold the samples into plaques (60 mm x 60 mm) to form parts.
[0094] [Table 13]
[0095]
[0084] Samples 23-26 were tested for mechanical properties and the results are shown in Table 14 below.
[0096] [Table 14]
[0097]
[0085] These and other modifications and variations of the present invention may be implemented by those skilled in the art without departing from the spirit and scope of the present invention. Moreover, it should be understood that aspects of the various embodiments may be interchanged in whole or in part. Moreover, those skilled in the art will recognize that the above description is for illustrative purposes only and is not intended to limit the invention as further described in the appended claims.
Claims
1. 1. A camera module comprising a polymer composition comprising a polymer matrix comprising a liquid crystal polymer and an inorganic filler, the liquid crystal polymer comprising repeat units derived from naphthenic hydroxy carboxylic acids and / or dicarboxylic acids in an amount of about 10 mole % or more of the polymer, and further comprising a polymer composition having a 400 second melting point according to ISO Test No. 11443:2005. -1 and a temperature 15° C. higher than the melting point of the composition, the composition having a melt viscosity of about 30 to about 400 Pa·s.
2. 10. The camera module of claim 1, wherein the polymer composition exhibits a flexural modulus of greater than or equal to about 7,000 MPa as determined at 23°C according to ISO Test No. 178:2010.
3. 10. The camera module of claim 1, wherein the polymer composition exhibits a Rockwell surface hardness of about 25 or greater as determined according to ASTM-D785-08 (scale M).
4. The polymer composition has a thermal conductivity of about 2 kJ / m2 as determined at 23° C. according to ISO test number 179-1:2010 2 2. The camera module of claim 1, exhibiting a Charpy notch free impact strength of 0.1 to 0.5 mm.
5. 10. The camera module of claim 1, wherein the polymer composition exhibits a tensile strength of about 20 to about 500 MPa, a tensile break strain of about 0.5% or greater, and / or a tensile modulus of about 5,000 MPa to about 30,000 MPa, as determined according to ISO Test No. 527:2012.
6. 10. The camera module of claim 1, wherein the polymer composition exhibits a dynamic coefficient of friction of about 1.0 or less and / or an abrasion depth of about 500 micrometers or less, as determined according to VDA-230-206:2007.
7. The camera module of claim 1 , wherein the polymer matrix comprises from about 20% to about 70% by weight of the polymer composition.
8. The camera module of claim 1 , wherein the liquid crystal polymer has a melting point of about 200° C. or higher.
9. 2. The camera module of claim 1, wherein the liquid crystal polymer comprises one or more repeat units derived from a hydroxycarboxylic acid, the hydroxycarboxylic acid repeat units making up about 50 mole % or more of the polymer.
10. 10. The camera module of claim 9, wherein the liquid crystal polymer comprises repeat units derived from 4-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, or a combination thereof.
11. 11. The camera module of claim 10, wherein the liquid crystal polymer comprises repeat units derived from 4-hydroxybenzoic acid in an amount of about 50 mol % to about 90 mol % of the polymer, and comprises repeat units derived from 6-hydroxy-2-naphthoic acid in an amount of about 10 mol % to about 50 mol % of the polymer.
12. 11. The camera module of claim 10, wherein the liquid crystal polymer further comprises repeat units derived from terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, hydroquinone, 4,4'-biphenol, acetaminophen, 4-aminophenol, or combinations thereof.
13. 9. The camera module of claim 8, wherein the polymer composition further comprises a semi-crystalline polyester comprising poly(ethylene terephthalate), poly(1,4-butylene terephthalate), poly(1,3-propylene terephthalate), poly(1,4-butylene 2,6-naphthalate), poly(ethylene 2,6-naphthalate), poly(1,4-cyclohexylene dimethylene terephthalate), derivatives of any of the above, or combinations thereof.
14. 14. The camera module of claim 13, wherein the liquid crystal polymer comprises from about 15% to about 85% by weight of the polymer composition, and the semi-crystalline polyester comprises from about 1% to about 50% by weight of the polymer composition.
15. 2. The camera module of claim 1, wherein the inorganic filler comprises about 20 to about 100 parts by weight per 100 parts by weight of the polymer matrix.
16. The camera module of claim 1 , wherein the inorganic filler has a hardness value of about 2.0 or greater on the Mohs hardness scale.
17. The camera module of claim 1 , wherein the inorganic filler comprises inorganic particles, inorganic fibers, or a combination thereof.
18. The camera module of claim 17, wherein the inorganic particles have a median diameter of about 0.5 to about 20 micrometers.
19. The camera module of claim 17 , wherein the inorganic particles comprise barium sulfate, calcium sulfate, silica, or a combination thereof.
20. 20. The camera module of claim 17, wherein the inorganic particles are flake-shaped particles having an aspect ratio of about 4 or greater.
21. The camera module of claim 17 , wherein the inorganic particles include mica.
22. The camera module of claim 17 , wherein the inorganic fibers comprise wollastonite fibers.
23. 10. The camera module of claim 1, wherein the polymer composition comprises a blend of inorganic particles and inorganic fibers, the inorganic fibers comprising from about 1% to about 40% by weight of the polymer composition, and the inorganic particles comprising from about 2% to about 50% by weight of the polymer composition.
24. The camera module of claim 1 , wherein the polymer composition is generally free of glass fibers.
25. The camera module of claim 1 , wherein the polymer composition includes an impact modifier.
26. 26. The camera module of claim 25, wherein the impact modifier comprises an olefin polymer.
27. 26. The camera module of claim 25, wherein the olefin polymer is a copolymer comprising (meth)acrylic acid monomer units.
28. The camera module of claim 1 , wherein the polymer composition comprises an antistatic filler.
29. 10. The camera module of claim 1, wherein the polymer composition comprises a tribological agent, a lubricant, a thermally conductive filler, a pigment, an antioxidant, a stabilizer, a surfactant, a wax, a flame retardant, an anti-sag additive, a nucleating agent, or a combination thereof.
30. The camera module includes: A housing having a lens module disposed therein, the lens module including one or more lenses; and Optionally, an actuator assembly configured to drive the lens module along an optical axis; Including; The camera module of claim 1 , wherein at least a portion of the housing, lens module, actuator assembly, or combination thereof comprises the polymer composition.
31. The actuator assembly is disposed between the housing and the lens module.
31. The camera module of claim 30, comprising a guide unit positioned on the camera body, the guide unit comprising a spring, a ball bearing, an electrostatic force generator, a hydraulic force generator, or a combination thereof.
32. The camera module of claim 31 , wherein at least a portion of the guide unit comprises the polymer composition.
33. The camera module of claim 31 , wherein the guide unit includes a ball bearing.
34. 34. The camera module of claim 33, wherein the ball bearings have an average dimension of about 800 micrometers or less.
35. 10. The camera module of claim 1, wherein the polymer composition exhibits a depression of about 50 micrometers or less when a metal ball having a diameter of 1.5 mm and a weight of 75 grams is dropped from a height of 15 centimeters into contact with the polymer composition.
36. An electronic device comprising the camera module according to claim 1 .
37. 37. The electronic device of claim 36, wherein the device is a wireless communication device.
38. 1. A polymer composition for use in a camera module, the composition comprising: a polymer matrix comprising a liquid crystal polymer, the liquid crystal polymer comprising repeat units derived from naphthenic hydroxy carboxylic acids and / or dicarboxylic acids in an amount of about 10 mole % or more of the polymer; about 1% to about 40% by weight of inorganic fibers; and about 2% to about 50% by weight of inorganic particles; Including; The polymer composition is subjected to a 400 second test according to ISO test number 11443:2005. -1 and a temperature 15° C. above the melting point of said composition, of about 30 to about 400 Pa·s.
39. 40. The polymer composition of claim 38, wherein the polymer composition exhibits a flexural modulus of greater than or equal to about 7,000 MPa as determined at 23°C according to ISO Test No. 178:2010.
40. 40. The polymer composition of claim 38, wherein said polymer composition exhibits a Rockwell surface hardness of about 25 or greater as determined according to ASTM-D785-08 (scale M).
41. The polymer composition has a thermal conductivity of about 2 kJ / m2 as determined at 23° C. according to ISO test number 179-1:2010 2 40. The polymer composition of claim 38, exhibiting a Charpy unnotched impact strength of
42. 39. The polymer composition of claim 38, wherein the polymer composition exhibits a tensile strength of about 20 to about 500 MPa, a tensile strain at break of about 0.5% or greater, and / or a tensile modulus of about 5,000 MPa to about 30,000 MPa, as determined according to ISO Test No. 527:2012.
43. The liquid crystal polymer comprises one or more repeat units derived from a hydroxycarboxylic acid, the hydroxycarboxylic acid repeat units making up at least about 50 mole percent of the polymer.
39. The polymer composition of claim 38.
44. 44. The polymer composition of claim 43, wherein the liquid crystalline polymer comprises repeat units derived from 4-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, or a combination thereof.
45. 45. The polymer composition of claim 44, wherein the liquid crystal polymer comprises repeat units derived from 4-hydroxybenzoic acid in an amount from about 50 mol % to about 90 mol % of the polymer and comprises repeat units derived from 6-hydroxy-2-naphthoic acid in an amount from about 10 mol % to about 50 mol % of the polymer.
46. 46. The polymer composition of claim 45, wherein the liquid crystal polymer further comprises repeat units derived from terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, hydroquinone, 4,4'-biphenol, acetaminophen, 4-aminophenol, or combinations thereof.
47. 39. The polymeric composition of claim 38, wherein the polymeric composition further comprises a semi-crystalline polyester comprising poly(ethylene terephthalate), poly(1,4-butylene terephthalate), poly(1,3-propylene terephthalate), poly(1,4-butylene 2,6-naphthalate), poly(ethylene 2,6-naphthalate), poly(1,4-cyclohexylene dimethylene terephthalate), derivatives of any of the foregoing, or combinations thereof.
48. 40. The polymer composition of claim 38, wherein the inorganic particles comprise barium sulfate, calcium sulfate, or a combination thereof.
49. 40. The polymer composition of claim 38, wherein said inorganic fibers comprise wollastonite fibers.
50. 40. The polymer composition of claim 38, wherein the polymer composition is free of glass fibers.
51. 39. The polymer composition of claim 38, wherein the polymer composition comprises a tribological agent, an impact modifier, an epoxy resin, an antistatic filler, a lubricant, a thermally conductive filler, a pigment, an antioxidant, a stabilizer, a surfactant, a wax, a flame retardant, an anti-sag additive, a nucleating agent, or a combination thereof.
52. 40. The polymer composition of claim 38, wherein the polymer composition exhibits an indentation of about 50 micrometers or less when a metal ball having a diameter of 1.5 mm and a weight of 75 grams is dropped from a height of 15 centimeters into contact with the polymer composition.
53. 40. The polymer composition of claim 38, wherein the polymer composition exhibits an indentation of about 50 micrometers or less when a metal ball having a diameter of 1.5 mm and a weight of 5 grams is dropped from a height of 150 millimeters into contact with the polymer composition 10,000 times.
54. A ball bearing comprising the polymer composition of claim 38, the ball bearing having an average dimension of less than about 800 micrometers.